Taqwim Barnamaj 'Arabiyyatiyy Fi Iksab Mufradat al-Lughat al-'Arabiyyah Lada al-Darisin al-Natiqin Bi Ghayriha - Nurkhamimi, Zainuddin; Muhammad Sabri, Sahrir; Mohd Shahrizal, Nasir (2015)
This study presents the evaluation procedures of Arabic vocabulary courseware namely “ cArabiyyatiyy” for non-Arabic students at the beginner’s level. This study employs an evaluative method in conducting its research procedures. 40 level one students from the Center for Foundation Studies, International Islamic University Malaysia had participated in the study which was carried out during the semester two of 2012/2013 academic year. The results of the vocabulary tests also show the success of multimedia program in the process of teaching and learning Arab vocabulary, since most of the students obtained good results in their post-tests conducted throughout the study. The study concludes that multimedia program can be used by all non-Arabic students regardless of their categories and backgrounds.